2018
DOI: 10.1016/j.eswa.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Complex correntropy function: Properties, and application to a channel equalization problem

Abstract: The use of correntropy as a similarity measure has been increasing in different scenarios due to the well-known ability to extract high-order statistic information from data. Recently, a new similarity measure between complex random variables was defined and called complex correntropy. Based on a Gaussian kernel, it extends the benefits of correntropy to complex-valued data. However, its properties have not yet been formalized. This paper studies the properties of this new similarity measure and extends this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…E[ • ] is the expected value operator. The work presented in [8] demonstrated that the complex correntropy generalizes the regular correntropy concept to complex-valued data while keeping important properties such as symmetry, bounded, high-order statistical measure, and a probabilistic meaning, specially when the complex Gaussian kernel, defined in (2) is used.…”
Section: Complex Correntropymentioning
confidence: 99%
See 4 more Smart Citations
“…E[ • ] is the expected value operator. The work presented in [8] demonstrated that the complex correntropy generalizes the regular correntropy concept to complex-valued data while keeping important properties such as symmetry, bounded, high-order statistical measure, and a probabilistic meaning, specially when the complex Gaussian kernel, defined in (2) is used.…”
Section: Complex Correntropymentioning
confidence: 99%
“…Figure 1 summarizes a system identification problem in which the MCCC was successful applied in [7]. The MCCC has been also applied to a channel equalization problem [8], but always employing a fixed-point solution algorithm. This approach depends on a matrix inversion, and this operation is sometimes unavailable or the increase in the computational cost is not ideal [13].…”
Section: Maximum Complex Correntropy Criterion (Mccc)mentioning
confidence: 99%
See 3 more Smart Citations